2012
DOI: 10.1007/s13204-012-0169-6
|View full text |Cite
|
Sign up to set email alerts
|

Simple glucose reduction route for one-step synthesis of copper nanofluids

Abstract: One-step method has been employed in the synthesis of copper nanofluids. Copper nitrate is reduced by glucose in the presence of sodium lauryl sulfate. The synthesized particles are characterized by X-ray diffraction technique for the phase structure; electron diffraction X-ray analysis for chemical composition; transmission electron microscopy and field emission scanning electron microscopy for the morphology; Fourier-transform infrared spectroscopy and ultraviolet-visible spectroscopy for the analysis of ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The peaks located at 232.4 eV are indicative of the presence of Mo 6+ (typically of MoO, BE value of 232.3–232.8 eV) . While the Mo 3d5/2 peaks located at 230.4 and 228.7 eV (typically Mo 4+ of MoS, BE value of 228.3–229.0 eV) are possibly related with the surface reduction of Mo 6+ caused by Cu + oxidation, the reducing nature of glucose or possible charge transfer from the carbon layer at surface . For samples discharged/charged to different stages, the dominant Mo 3d5/2 peak is located at 232.2–232.3 eV, correlating to the dominance of Mo 6+ .…”
Section: Resultsmentioning
confidence: 97%
“…The peaks located at 232.4 eV are indicative of the presence of Mo 6+ (typically of MoO, BE value of 232.3–232.8 eV) . While the Mo 3d5/2 peaks located at 230.4 and 228.7 eV (typically Mo 4+ of MoS, BE value of 228.3–229.0 eV) are possibly related with the surface reduction of Mo 6+ caused by Cu + oxidation, the reducing nature of glucose or possible charge transfer from the carbon layer at surface . For samples discharged/charged to different stages, the dominant Mo 3d5/2 peak is located at 232.2–232.3 eV, correlating to the dominance of Mo 6+ .…”
Section: Resultsmentioning
confidence: 97%
“…It was observed that CuNW/PVDF had higher dielectric permittivity and lower dielectric loss than the MWCNT/PVDF nanocomposites at room temperature. Copper nanoparticles were usually utilized for improving the thermal properties of nanofluid with different base fluid [22][23][24][25]. Zeng et al [26] investigated the effect of copper nanowires with ultrahigh aspect ratio and sponge-like structure on the properties of organic phase change materials, and the thermal conductivity of the composite enhanced greatly compared with base materials.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…The observed trend can be explained as follows. With the increase in the dilution, the overall concentration of the species decreases, the proximity between the precipitating atoms decreases and hence the collision between them is reduced, preventing the growth of particle and hence resulting in smaller size of the nanoparticles formed [11].…”
Section: Effect Of Dilutionmentioning
confidence: 99%